MODERN ASPECTS OF DIAGNOSTICS AND TREATMENT OF FACIAL PAIN - Tufliev Azimjon Abdirahim ugli; Abdumajidov Muzaffar Abdulkhaevich (Scholar Express Journals, 2025)
Atypical facial pain is the least studied variant of prosopalgia (facial pain), since several mechanisms are involved in its development, and the psychogenic component is considered the main one. The disease is most often associated with depression, anxiety disorders, and other mental illnesses. To date, other predisposing and provoking factors of pathology have been established.
Keywords: nociceptive; neuropathic; psychogenic